Unlocking Job Performance: How Servant Leadership, Psychological Safety, and Organizational Justice Drive Success Through Organizational Trust - Nurul Badriyah; Abu Muna Almaududi Ausat; Muhammad Aqib Shafiq; Doaa Wafik; Mohammed Mudher Mazil (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: In Surabaya's competitive MSME market, employee performance is essential to the success of the company. Resource limitations, high employee turnover, and the requirement for flexible tactics in ever-changing markets are some of the difficulties faced by MSMEs. Servant leadership, which emphasises the growth and well-being of employees, has become a crucial strategy. Building psychological safety, organisational fairness, and trust is crucial for promoting good performance because they create an atmosphere where workers feel appreciated and inspired to give their all.Purpose: The purpose of this study is to examine and assess how organisational justice, psychological safety, and servant leadership affect worker performance in MSMEs in Surabaya. It also looks at how organisational trust functions as a mediator in these connections, offering insights into how these elements work together to affect employee performance. Design/methodology/approach: The SEM-PLS methodology is used in this quantitative study to investigate the correlations between the pertinent variables. 110 MSMEs in Surabaya, Indonesia, were the subject of the study, which used an online questionnaire to gather data.Findings/Result: According to this study, job performance is greatly impacted by organisational justice, psychological safety, and servant leadership, with organisational trust serving as a mediating factor. In particular, organisational justice and psychological safety boost performance by promoting trust, whereas servant leadership improves job performance by establishing organisational trust. To mediate these connections, trust is essential.Conclusion: The conclusion highlights how job performance in MSMEs may be greatly improved by cultivating organisational trust through organisational justice, psychological safety, and servant leadership. When paired with a fair and psychologically secure workplace, servant leadership techniques that support staff growth increase organisational trust. Consequently, this trust has a good impact on worker productivity, quality, and creativity.Originality/value (State of the art): Although similar studies have been done, this study adds new insights by integrating servant leadership, psychological safety, and organisational justice with an emphasis on trust as a mediator. This research advances our understanding of how organisational trust mediates the relationships between leadership styles, workplace safety, and justice concerning job performance, especially in MSMEs. Keywords: job performance, organizational justice, organizational trust, psychological safety, servant leadership